Упростите и найдите 12x-(4y+(3x-(5y-2x))) при x=-13/14 y=3,1
Упростите и найдите
12x-(4y+(3x-(5y-2x)))
при x=-13/14
y=3,1
Ответ(ы) на вопрос:
[latex]12x-(4y+(3x-(5y-2x)))=12x-(4y+(3x-5y+2x))=[/latex]
[latex]=12x-(4y+(5x-5y))=12x-(4y+5x-5y)=12x-(5x-y)=[/latex]
[latex]=12x-5x+y=7x+y[/latex]
если х=-13/14, у=3,1, то [latex]7x+y=7*(- \frac{13}{14} )+3,1=- \frac{13}{2}+3,1=-6,5+3,1=-3,4 [/latex]
12x-(4y+(3x-(5y-2x)=12x-(4y+(3x-5y+2x))=12x-(4y+3x-5y+2x)=12x-4y-3x+5y-2x=y+7x
Если x=-13/14;y=3,1; то 3,1+(-13/14)=3,1-6,5=-3,4
Не нашли ответ?
Похожие вопросы